ELEMENTARY EDUCATION PROGRAMS TEACHERS AND MTB MLE IMPLEMENTATION IN THE PHILIPPINES - Paz, Rafael Michael O (PEOPLE: International Journal of Social Sciences, 2018)
According to the new The K to 12 Basic Education Program implemented in the Philippines in 2013, modifications in pre-service education for aspiring teachers shall be applied to conform to the requirements of both K to 12 and its auxiliary program for the first three levels called Mother Tongue-Based Multilingual Education (MTB-MLE) that mandates the utility of students’ mother tongue(s) as medium of instruction. The agencies in charge for these modifications are the Department of Education and the Commission on Higher Education. Their task involves ensuring that the Teacher Education curriculum offered in different higher education institutions in the Philippines will meet the necessary quality standards for new teachers. However, since the implementation of MTB-MLE as a national policy in the School Year 2012-2013, no national guideline has been issued to higher education institutions regarding the said modifications.This paper locates voices of tertiary instructors employed in elementary education programs in four selected universities across the Philippines during the implementation of the MTB-MLE policy. This study specifically sought to determine the interventions applied by university administrations to their elementary education programs to ensure that their adult learners’ knowledge and skills are aligned with the national policies even without direct guidelines from any macro agents. Central to this paper are the perceptions of the informants regarding the interventions applied by their university administrations to their elementary education programs.